Environmental Management for Malaria Control in the East Asia and Pacific (EAP) Region - Lindsay, Steve (World Bank, Washington, DC, 2013)
Malaria attacks millions in the East Asia and Pacific (EAP) region, and greatly impedes economic development, particularly affecting the rural poor. In the early 1900s malaria was controlled in many parts of the region using environmental management (EM) for vector control. EM is where the environment is modified or manipulated to reduce malaria transmission by attacking local vector mosquitoes and requires an understanding of the ecology of these species. Today malaria control is based on drugs and insecticides, but their sustainability has been undermined by the development of resistance and growing concerns about the long-term environmental impact of some insecticides. EM would strengthen malaria control activities and be cost-effective. To be successful EM requires co-ordination and collaboration between different public sectors. This document presents the options that exist to minimize malaria risks associated with infrastructure development projects. It also aims to raise awareness of the wide array of opportunities that exist to design, construct and operate infrastructure as a sustainable means of reducing malaria transmission risks in specific settings. Environmental management offers exciting new opportunities for sustainable malaria control throughout the EAP, not on it's own, but as part of an integrated approach to malaria management.